Should patients undergoing PCI still be consented for emergency bypass? - Arnold, JR; Karamitsos, T; Shirodaria, C; Banning, A (2009)
Informed consent for emergency coronary artery bypass grafting (CABG) is routinely obtained from patients undergoing percutaneous coronary intervention (PCI) and diagnostic angiography. Given the recent technological and pharmacological advances as well as increasing operator experience, we sought to assess the contemporary incidence of emergency CABG following PCI in our centre. In a total of 7855 consecutive PCIs, the overall rate of emergency CABG was 0.11%, and the mortality risk was 0.67%. We believe that in the vast majority of patients undergoing PCI and diagnostic angiography, routine consent for emergency CABG is no longer appropriate.